Possibilities for mountain-based adventure tourism: the case of Serbia - VujadinovićCDFMR Snežana; ŠabićCDFMR Dejan; JoksimovićCDFMR Marko; GolićCDFMR Rajko; GajićCDFMR Mirjana; ŽivkovićCDFMR Ljiljana; MilinčićCDFMR Miroljub (Bulletin of Geography. Socio-Economic Series, 2013)
Adventure tourism is a specific type of tourism that has been increasingly popular in Serbia in recent years. In this regard, the paper identifies the basic characteristics of adventure tourism, its development in Serbia, with a great emphasis placed on high mountain areas that, owing to their physical and geographic characteristics, possess huge potential. The paper aims, among other things, to identify factors encouraging or limiting development of adventure tourism in Serbia, analysing the practice, defining potential destinations and suggesting appropriate measures in order to promote it